The sacredness of the Maengket Dance in Contextual Theological Perspective - Agnes Relly Poluan; Nency Aprilia Heydemans; Alon Mandimpu Nainggolan (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
This article aims to interpret the reality of the sacredness of the Maengket dance in Minahasa culture from a contextual theological perspective. Maengket dance is an original Minahasa dance that contains some sacred values ??in the form of traditional rituals (foso) and performing arts. This study uses a qualitative approach through interviews, observations, and literature study. The research finding in this article is the encounter between the Bible and culture in Minahasa seen in dance. However, due to globalization, the meaning of sacredness and ethnic identity in the dance has experienced a shift in values. Therefore, it is concluded that the Maengket dance is part of the identity of the Minahasa tribe in offering prayers of supplication and thanksgiving to Opo Empung Wailan Wangko (God the Almighty), which is inclusive in people's daily lives. On the other hand, it is necessary to get attention from various parties to preserve this artwork as a legacy of local wisdom for the next Minahasa generation.